IS QUALITY OF LIFE WORSE IN PATIENTS WITH ADOLESCENT IDIOPATHIC SCOLIOSIS WHO UNDERGO LONGER FUSIONS? 2 YEARS OF FOLLOW-UP - Chaves Filho,Amauri (2022)
ABSTRACT Objective: To compare quality of life in patients with longer fusions with that of those who have short fusions 2 years of after surgery. Methods: This is a retrospective comparative cohort study (Level of Evidence III) involving patients with adolescent idiopathic scoliosis who underwent posterior spinal fusion with pedicle screws with a 2-year follow-up. The primary outcome was quality of life assessed using the SRS-30 questionnaire. Participants were divided according to Lenke and stratified into those with major (Lenke 3 and Lenke 6) and minor (Lenke 1 and Lenke 5) fusions. Results: Forty-one patients, 34 of whom were women, were evaluated: Lenke 1 (17 patients), Lenke 3 (15 patients), Lenke 5 (3 patients), and Lenke 6 (6 patients). The mean age was 13.8 years, the mean preoperative and postoperative Cobb angles were 56.48 degrees and 10.49 degrees, respectively, and the mean surgical Cobb reduction was 45.54 degrees. All patients in the sample showed an overall improvement in quality of life after surgery (p<0.0001). There was no difference between groups A (long fusions) and B (short fusions) in relation to the domains in general (p>0.05). Although pain was improved in the overall sample, this was not the case for the group with structured double curves and longer fusions (p = 0.03). Conclusion: There was no difference in quality of life between patients with long and short fusions with a 2-year follow-up. Level of Evidence III; Retrospective cohort.